What are consumer attitudes in urban India like towards ethical food products and what influences their attitudes? - Khara, Tani (Curtin University, 2015)
This study explores the attitudes of India’s urban middle class consumers towards ethical foods, while also understanding what influenced these attitudes. It revealed a range of diverse attitudes towards ethical foods, many of which were unique to Indian culture. While globalisation is transforming urban consumption habits, India’s consumers are also retaining their traditional values which, in turn, have influenced these attitudes. Against the backdrop of change, this study highlighted the role and significance of sustainable consumption in urban India.